Preparation of polymeric nanofibers via immersion electrospinning. (5th July 2020) - Wang, Xushan; Nakane, Koji
Graphical abstract: Schematic illustration of fiber solidification via non-solvent induced phase separation in immersion electrospinning. Highlights: Immersion electrospinning (I-ESP) is a greener technique for nanofiber preparation. Hexane is considered to be the most suitable medium among tested liquids as the coagulation bath for I-ESP. I-ESP can produce ultrafine nanofibers while collecting distance is within a few centimeters. Fast precipitation of polymers favors the production of smooth nanofibers. I-ESP is generally applicable to fabricate nanofibers from commonly used polymers. Abstract: Electrospinning is a simple and highly versatile method in manufacturing nanoscale fibers from a wide range of materials including metals, ceramics, and polymers. However, conventional electrospinning, in some applications of nanofiber production especially from water-insoluble polymers, could be considered as a harmful process. Since in traditional solution electrospinning nanofibers are formed through the evaporation of volatile and toxic solvents, which produces harmful gas and leads to environmental pollution. The accompanying pollution becomes more serious when it comes to large-scale manufacturing of nanofibers via electrospinning. Here, we apply a greener electrospinning method coined as Immersion Electrospinning (I-ESP) that applies phase separation to solidify spinning jets into nanofibers rather than solvent volatilization. In this study, I-ESP has been successfully exploited to fabricate nanofibers from poly(vinyl alcohol), poly(vinylidene fluoride), cellulose acetate, and poly(acrylic acid) with the hexane coagulation bath. The influence of polymer solution properties and coagulation bath composition on the morphology of nanofibers has been investigated.